Effect of humidity on evaporation from aqueous and nonaqueous microemulsion with perfume - Hamdan, S.; Ahmad, F.B.H.; Dai, Y.Y.; Dzulkefly, K.; Ku Bulat, K.H. (Informa UK Limited, 1999)
The weight loss during evaporation from an aqueous and nonaqueous microemulsion with limonene was followed gravimetrically at two different humidities. Result showed that at lower humidity the weight loss is greater for both of the systems. The weight loss is a however, higher for the aqueous counterpart.